The influence of natural humidity upon the index of the compression of limnoglacial clay/Natūraliojo drėgnio įtaka limnoglacialinio molio kompresijos koeficientui - Alikonis, Antanas (Journal of Civil Engineering and Management, 2001)
The coefficients of soil porosity and compressibility are not the only indices showing links between loading and squeezability. The index of compressibility is sometimes inconvenient for practical use. The graph of soil compressibility in the system of semi-logarithmic co-ordinations is a straight line, that’s why the index of compressibility which is determined by it is a constant quantity and can be applied for a big interval of loading. The index of compressibility is very often defined as the interval the beginning of which is relictic pressure and is used to calculate the deformations of the soil layer when the loadings are bigger [2, 3]. The index of compressibility is different not only for different types of soil but for the same type of soil too, depending on the indices of its condition, its mineral composition and the peculiarities of its formation. The author of this article has investigated the influence of natural and fluid humidity upon the compression coefficient of Lithuanian limnoglacial clays. The natural soil humidity was defined according to the standard method as the ratio of water mass which is in soil and the mass of solid particles. Lithuanian limnoglacial clay from Jūros-Šešupės, Kauno-Kaišiadorių, Mūšos and Dysnos main basins was used for investigations. The plasticity index of solid soils was bigger than 17, water saturation level was 0.8–1. Hydro-mica (average 65–75%) and kaolin (average 10–20%) composed the mineral structure of limnoglacial clay. The index of compressibility was calculated by working up the results of investigations. Most often the calculable interval was between the tensions σ = 0.2 Mpa and σ = 0.4 Mpa. The calculated index of compressibility Cc is connected with the natural humidity W of that soil. The values of coefficient k were calculated according to humidity and the compressibility index. A formula to calculate the index of compressibility was obtained. The values of natural humidity W of solid soil varied from 10 up to 39%, the values of the calculated index of compressibility Cc from 0.13 up to 0.24, and the values of coefficient k varied from 0.0033 up to 0.0066. Article in Lithuanian. First Published Online: 30 Jul 2012